2018
DOI: 10.15666/aeer/1603_30613078
|View full text |Cite
|
Sign up to set email alerts
|

Shrimp and Fish Catch Landing Trends in Songkhla Lagoon, Thailand During 2003-2016

Abstract: Abstract. Time series analysis techniques and Seasonal Autoregressive Integrated Moving Average (SARIMA) models were used to analyze monthly fish and shrimp catch landing trends recorded for Songkhla shallow lagoon in Thailand (2003Thailand ( -2016. Autocorrelation (AC) and Partial Autocorrelation (PAC) functions were calculated to build seasonal ARIMA models. These models were well-chosen for explaining the time series and forecasting future catch landings. It is found that both fish and shrimp catch landings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Modeling to predict the number of new cases in the next days is one way that reveals the trend of disease. Artificial Neural Networks (ANN) and Auto-Regressive Integrated Moving Average (ARIMA) are the two most popular class of models for trend modeling and predicting time-series data ( 17 ) Although ARIMA has been in use for forecasting infectious disease since past years ( 18 ), ANN has been recently known as powerful nonlinear regression techniques( 19 ); and due to its ability for time series forecasting, it has been widely applied ( 20 ). ANN is a member of machine learning algorithms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modeling to predict the number of new cases in the next days is one way that reveals the trend of disease. Artificial Neural Networks (ANN) and Auto-Regressive Integrated Moving Average (ARIMA) are the two most popular class of models for trend modeling and predicting time-series data ( 17 ) Although ARIMA has been in use for forecasting infectious disease since past years ( 18 ), ANN has been recently known as powerful nonlinear regression techniques( 19 ); and due to its ability for time series forecasting, it has been widely applied ( 20 ). ANN is a member of machine learning algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies confirmed the superior performance of machine learnig algorithms in comparison to more customary models ( 21 ). However, none of ARIMA and ANN has been definitively proven to be more precise than the other for different medical fields; and therefore studies continue to compare them ( 17 ). This comparison is also continued in this study to determine the most accurate model for forecasting the spreading trend of Coronavirus.…”
Section: Introductionmentioning
confidence: 99%
“…About 13.75% fishing zone has been encroached enclosures '(Gherries), reduction in flushing flow frequencies by diverting inland flow and changing the hydrologic regimes (Gobkund cut), over exploited aqua catch with inappropriate fishing gears, more motorized boats for ecotourism; restricting fish migration; and finally ambient water quality deterioration need to be attended. Knowledge of ambient living requirements like seasonality, salinity gradient, water exchange, phytoplankton expanse and anthropogenic activities is needed along with forecasting play important role in fisheries and fish management as they institute the various steps to build strategic decision, (Stergiou, et al [52] and Hue, et al [53]). A major portion of the lagoon is encroached by human habitation, tourism, prawn farms (≈ more than 15%).…”
Section: Discussionmentioning
confidence: 99%
“…for disease management studies 33,34 . Previous study revealed that ARIMA is one of the most suitable models as it has higher fitting and forecasting accuracy 35,36 . In recent years, it is also an useful model for predicting the incidence of infectious disease 20 The prediction indicates an upward trend for daily total confirmed cases along with total deaths.…”
Section: Discussionmentioning
confidence: 99%
“…The estimation of infectious disease like COVID-19 management by developing hypothesis for interpreting the observed situation can be done via time series analysis 32 .Time series health researchers widely use ARIMA model because of the importance of ‘time’ for disease management studies 33,34 . Previous study revealed that ARIMA is one of the most suitable models as it has higher fitting and forecasting accuracy 35,36 . In recent years, it is also an useful model for predicting the incidence of infectious disease 20 .…”
Section: Discussionmentioning
confidence: 99%